The fragrant companions : a play about love between women - Li, Yu, 1611-1680?; Roddy, Stephen; Wang, Ying, 1955 December 26- (New York : Columbia University Press, 2022)
"Written in 1651, The Fragrant Companions is the first of ten extant chuanqi plays by Li Yu. The play, told in 36 acts, is one of the only literary works of pre-modern China that focuses on the theme of lesbian love. The play tells the story of two young ladies of the gentry who fall in love with each other after exchanging poems in a nunnery and overcome different obstacles to be together through a recognized marriage-by marrying the same husband. While its finale of a heterosexual marriage seems to reconcile with the Confucian gender ideology, polygamy, and the patriarchal social order, the play is really about the two women's genuine love and passion for each other; their mutual longing when separated; their efforts and resourcefulness to surmount social bias and impediments; and the triumph of their love over social mandates and expectations"--
Intro -- Table of Contents -- Introduction: Women in Love and the Business of Men in Li Yu's Chuanqi Drama -- Dramatis Personae -- The Relationship Between Role Types and Characters -- Note on Editions of Lianxiangban -- List of Scenes -- The Fragrant Companions -- Appendix: Modes and Tunes -- Notes -- Selected Works on Li Yu and Same-Sex Love in Classical Chinese Fiction and Drama -- Index
Includes bibliographical references and index
Description based on print version record
eBooks on EBSCOhost
Keywords: Li, Yu, -- 1611-1680? -- Translations into English; Li, Yu, -- 1611-1680?; Lesbians -- Drama; Triangles (Interpersonal relations) -- Drama; LITERARY COLLECTIONS / Asian / Chinese; Lesbians; Triangles (Interpersonal relations); Drama; Lesbian drama; Translations; Lesbian drama